Partner Substitutability, Alliance Network Structure, and Firm Profitability in the Telecommunications Industry - Bae, Jonghoon; Insead, Martin Gargiulo (Academy of Management Journal, 2004)
This paper explores the effects of partner substitutability and alliance network structure on organizational profitability. Although firms are expected to benefit from the exclusive resources brought in by resource-rich, nonsubstitutable alliance partners, the costs of allying with such partners could offset those benefits. Analyzing alliances in the U.S. telecommunications industry, we show that a firm facing nonsubstitutable partners was better off when its alliances were embedded in third-party ties, which allowed the firm to gain indirect leverage on such partners.